Estrogen receptor β1 in diffuse large B-cell lymphoma growth and as a prognostic biomarker. Issue 2 (1st February 2017) - Hasni, Muhammad Sharif; Berglund, Mattias; Yakimchuk, Konstantin; Guan, Jiyu; Linderoth, Johan; Amini, Rose Marie; Enblad, Gunilla; Okret, Sam
Abstract: Diffuse large B-cell lymphoma (DLBCL) shows a higher incidence in males versus females. Epidemiological studies have shown that female gender is a favorable prognostic factor, which may be explained by estrogens. Here we show that when grafting human DLBCL cells to immunocompromised mice, tumor growth in males is faster. When treating mice grafted with either germinal center or activated B-cell like DLBCL cells with the selective estrogen receptor β (ERβ) agonist diarylpropionitrile, tumor growth was significantly inhibited. Furthermore, nuclear ERβ1 expression analysis in primary DLBCL's by immunohistochemistry revealed expression in 89% of the cases. Nuclear ERβ1 expression was in a univariate and multivariate analysis, an independent prognostic factor for adverse progression-free survival in Rituximab-chemotherapy treated DLBCL ( p  = 0.02 and p  = 0.04, respectively). These results suggest that estrogen signaling through ERβ1 is an interesting future therapeutic target for treatment of DLBCL, and that ERβ1 expression can be used as a prognostic marker.